Changes in serum BDNF levels after treatment of panic disorder patients (Annals of Medical Research, 2021)
Aim: Panic disorder is a significant psychiatric disorder that more frequently occurs in women, with daily attacks such as fear of death, limiting the patient’s daily life. It is often associated with agoraphobia. The aim of this study was to investigate the relationship between BDNF levels and the clinical features of panic disorder.Material and Methods: The study was carried out between January 2015 and July 2015 with 42 female patients and 38 healthy females who were admitted to Psychiatry Outpatient Clinic. The patients who were diagnosed with panic disorder without agoraphobia included in the study. The Panic Disorder Severity Scale (PDSS) was applied to the patients. Serum BDNF was measured by sandwich ELISA.Results: The mean age of the 38 female patients was 35.1±11.5 years. The mean age of the control group of 38 healthy women was 34.9±9.82 years. Serum BDNF levels measured before treatment were significantly lower than BDNF levels measured after treatment (p 0.001). Serum BDNF levels measured before treatment were significantly lower than BDNF levels of the control group (p0.001). While there was a statistically significant negative correlation between BDNF levels and PDSS scores before treatment.Conclusion: Serum BDNF levels were significantly increased after treatment. The PDSS scores also decreased significantly after treatment. These results inform us about the effectiveness of the treatment. BDNF levels may also be considered as an indicator of the clinical follow-up of the panic disorder without agoraphobia.Keywords: Panic disorder; brain-derived neurotrophic factor; agoraphobia.